Literatura em rede nacional: a adaptação da obra A Muralha para a televisão - Borges, Samantha de Oliveira (2013)
This paper presents the analysis of the adaptation process of the book A Muralha, from author Dinah Silveira de Queiroz, to the miniseries format, written by Maria Adelaide Amaral. The literary narrative was ordered to Dinah as a tribute to 400 years anniversary of the city of São Paulo, which was in the year of 1954. The miniseries was broadcasted by Rede Globo de Televisão, in the year 2000, celebrating the 500 years of Brazil s discovery. A classical historical novel, the narrative performs a recall of the Paulista capital foundation time and its first pioneers, the bandeirantes. In order to understand the television transposition, initially we perform a theoretical revision that includes since the fundamentals of comparative literature until we get to the intermediality theory, also highlighting the way crossed by the adaptation since its cinematographic version until its television variety. The goal of this research is to analyze the adaptation starting with the elements listed by Robert Stam (2003): authorship, characters, exchanges and history and context modifications. Moreover, Stam grounds his methodological model in dialogism theories from Mikhail Bakhtin revisited by Julia Kristeva and in transtextuality by Gérard Genette, also used to justify the analysis. When we describe and analyze the textual elements that are modified, transformed, excluded or enlarged at the adaptive process of the literary narrative to the televisual narrative, we pick out, among the analysis elements, the hipertextuality that, according to Genette (2006), consists of every relationship that unites a text B (hypertext) to a previous text A (hypotext). At A Muralha adaptation, the literary work consists of a hypotext and the miniseries, a hypertext. In this light, the hypertextual narrative (miniseries) enlarges, modifies, transforms and recreates the textual characters, thematic, plots and times of the hypotextual narrative (book). From this, it is concluded that the adaptive process is set as a space of dialogue between the literature and other Medias, promoting different rereadings of the same narrative and stimulating the intermediatic capacity of the texts studied.